HYPOGLYCEMIA AND ITS CLINICOPATHOLOGICAL OUTCOME IN DIABETIC PATIENTS ADMITTED IN DHQ TEACHING HOSPITAL KOHAT - USMAN, M; SHAH, F (Biological and Clinical Sciences Research Journal, 2024)
Hypoglycemia is a common and serious complication in patients with diabetes, leading to adverse clinical outcomes. Understanding its frequency and associated clinicopathological outcomes is crucial for improving patient management and outcomes. Objective: To assess the frequency of hypoglycemia and its clinicopathological outcomes in admitted diabetic patients. Methods: A cross-sectional observational study was conducted at DHQ Teaching Hospital KDA, Kohat, from February 8-2023, to August 8-2023. The study included 110 patients diagnosed with diabetes. Clinicopathological outcomes were assessed, including hospital stay duration, readmissions, and mortality. Statistical analysis was performed to determine the association between hypoglycemia and these outcomes. Results: The frequency of hypoglycemia among the patients was 35.5% (39 patients). Hypoglycemia was notably associated with longer hospital stays (> 25 days), increased readmissions, and higher mortality rates. Conclusion: Hypoglycemia is a frequent condition observed in diabetic patients, significantly contributing to prolonged hospital stays, increased readmission rates, and mortality. Effective management strategies are necessary to reduce the incidence of hypoglycemia and improve patient outcomes.